Use of Soybean as Partial Substitute of Fish Meal in the Diets of Rohu, Labeo rohita (Ham.) fry (The Agriculturists, 2012)
A 60-day feeding trial was conducted in a static indoor rearing system in 12 glass aquaria to investigate the possibility of using soybean meal protein in lieu of fishmeal as dietary protein source for Labeo rohita fry. Four iso-nitrogenous (30% protein) and iso-caloric (19 kJ/g GE) experimental diets were prepared as: diet 1 (100% fishmeal protein), diet 2 (75% fishmeal protein + 25% soybean meal protein), diet 3 (50% fishmeal protein + 50% soybean meal protein) and diet 4 (25% fishmeal protein + 75% soybean meal protein) and were fed to triplicate groups of 10 fish (per aquarium). Fish were fed two times daily at a rate of 5% of their body weight during the entire experimental period. The feeding ration was adjusted every 10th day through sampling of fish. Growth rate, feed conversion ratio (FCR) and protein efficiency ratio (PER) were significantly higher (P0.05). The growth rates, FCR and PER as obtained from the different treatments indicate that fishmeal protein could be replaced up to 50% by soybean meal protein in the diet of L. rohita fry without supplementation of amino acids. DOI: http://dx.doi.org/10.3329/agric.v10i2.13143 The Agriculturists 2012; 10(2) 68-76